Educational Social Interaction in Learning Development at SMP ZIIS Cilongok - Herisnawan, Diky; Ningsih, Tutuk (Lembaga Riset Mutiara Akbar, 2024)
The educational interaction between teachers and students is a process of reciprocal, communicative relationships. At SMP ZIIS (Zamzam Integrated Islamic School) Cilongok, some students feel shy, fearful, or lack confidence to ask questions, resulting in less active social interaction between teachers and students in the classroom. This study aims to explain the role of educational social interaction in the development of learning at SMP ZIIS Cilongok. The research uses a qualitative-descriptive method. Data were collected through observation, interviews, and documentation, with analysis using data triangulation techniques. The findings indicate that educational social interaction plays a significant role in the development of learning at SMP ZIIS Cilongok. Through healthy and productive relationships between teachers and students, this interaction supports the achievement of academic goals and the development of student character, such as cooperation, responsibility, and discipline. The implementation of educational social interaction, which involves active communication and a conducive learning environment, has successfully created an effective learning atmosphere. Furthermore, the use of innovative learning media has enhanced the effectiveness of the learning process, which in turn contributes to the improvement of the overall quality of education at this school. Although there are several challenges in its implementation, continuous efforts are being made to improve its effectiveness.